Reproductive meltdowns underlie arthropod extinctions in the face of climate change - Michael P Moore; Sarah E Nalley; Noah T Leith (Current Opinion in Insect Science, 2026)

Carryover Effects on Reproduction Can Buffer Against Mortality‐Driven Population Declines at Elevated Developmental Temperatures - Noah T. Leith; Anthony Macchiano; Brigitte Tenhumberg; Inaya Smith; Jake P. Woods; Kasey D. Fowler‐Finn (Ecology Letters, 2025)
Carryover effects broadly influence adult performance and population persistence. Although variation in developmental environments can have contrasting effects on survival and reproduction, current predictive models of vulnerability to environmental change typically ignore simultaneous changes in both fitness components. We tested how developmental temperatures shape survival and multiple aspects of reproduction in a plant‐living insect ( Enchenopa binotata treehoppers) and used population dynamic models to examine the cumulative impact of these complex effects on population growth. We show that elevated developmental temperatures increase adult fertility, offsetting reduced juvenile survival and potentially forestalling population declines following global warming. Moreover, pairing mates from different developmental temperatures exacerbated morphological mismatches between sexes, reducing mating success and sperm transfer. Our findings thereby provide novel evidence that thermal carryover effects can generate assortative mating and selection on adult reproductive morphology, in addition to shaping the relative importance of survival and reproduction for persistence in warming climates.

Human‐modified habitats imperil ornamented dragonflies less than their non‐ornamented counterparts at local, regional, and continental scales - Michael P. Moore; Noah T. Leith; Kasey D. Fowler‐Finn; Kim A. Medley (Ecology Letters, 2024)
Biologists have long wondered how sexual ornamentation influences a species' risk of extinction. Because the evolution of condition‐dependent ornamentation can reduce intersexual conflict and accelerate the fixation of advantageous alleles, some theory predicts that ornamented taxa can be buffered against extinction in novel and/or stressful environments. Nevertheless, evidence from the wild remains limited. Here, we show that ornamented dragonflies are less vulnerable to extinction across multiple spatial scales. Population‐occupancy models across the Western United States reveal that ornamented species have become more common relative to non‐ornamented species over >100 years. Phylogenetic analyses indicate that ornamented species exhibit lower continent‐wide extinction risk than non‐ornamented species. Finally, spatial analyses of local dragonfly assemblages suggest that ornamented species possess advantages over non‐ornamented taxa at living in habitats that have been converted to farms and cities. Together, these findings suggest that ornamented taxa are buffered against contemporary extinction at local, regional, and continental scales.

Evolutionary interactions between thermal ecology and sexual selection - Noah T. Leith; Kasey D. Fowler‐Finn; Michael P. Moore (Ecology Letters, 2022)
Thermal ecology and mate competition are both pervasive features of ecological adaptation. A surge of recent work has uncovered the diversity of ways in which temperature affects mating interactions and sexual selection. However, the potential for thermal biology and reproductive ecology to evolve together as organisms adapt to their thermal environment has been underappreciated. Here, we develop a series of hypotheses regarding (1) not only how thermal ecology affects mating system dynamics, but also how mating dynamics can generate selection on thermal traits; and (2) how the thermal consequences of mate competition favour the reciprocal co‐adaptation of thermal biology and sexual traits. We discuss our hypotheses in the context of both pre‐copulatory and post‐copulatory processes. We also call for future work integrating experimental and phylogenetic comparative approaches to understand evolutionary feedbacks between thermal ecology and sexual selection. Overall, studying reciprocal feedbacks between thermal ecology and sexual selection may be necessary to understand how organisms have adapted to the environments of the past and could persist in the environments of the future.

Forced running-induced rhabdomyolysis in the Sprague–Dawley rat: towards a rodent model of capture myopathy - Crystal Lubbe; Brian H. Harvey; Francois P. Viljoen; Leith Meyer; De Wet Wolmarans (Veterinary Research Communications, 2021)

Ameliorating the adverse cardiorespiratory effects of chemical immobilization by inducing general anaesthesia in sheep and goats: implications for physiological studies of large wild mammals - Adian Izwan; Edward P. Snelling; Roger S. Seymour; Leith C. R. Meyer; Andrea Fuller; Anna Haw; Duncan Mitchell; Anthony P. Farrell; Mary-Ann Costello; Shane K. Maloney (Journal of Comparative Physiology B, 2018)

Boundary spanning at the science–policy interface: the practitioners’ perspectives - A. T. Bednarek; C. Wyborn; C. Cvitanovic; R. Meyer; R. M. Colvin; P. F. E. Addison; S. L. Close; K. Curran; M. Farooque; E. Goldman; D. Hart; H. Mannix; et al. (Sustainability Science, 2018)

Towards a diagnostic approach to climate adaptation for fisheries - P. Leith; E. Ogier; G. Pecl; E. Hoshino; J. Davidson; M. Haward (Climatic Change, 2014)